Interest rates, distribution and capital accumulation: A Post-Kaleckian perspective on the US and Germany - Eckhard Hein; Christian Schoder (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2009)
We analyse the effects of interest rate variations on the rates of capacity utilisation, capital accumulation and profit in a simple post-Kaleckian distribution and growth model. This model gives rise to different potential accumulation regimes depending on the values of the parameters in the investment, saving and distribution function. Estimating these core behavioural equations for the US and Germany in the period 1960-2007, we find significant and robust effects of interest payments with the expected sign in each of the equations. Our estimation results imply, both for the US and for Germany, that the effects of changes in the real long-term rate of interest on the equilibrium rates of capacity utilisation, capital accumulation and profits are characterised by the 'normal regime': Rising long-term real rates of interest cause falling rates of capacity utilisation, capital accumulation and profits, as well as redistribution at the expense of labour income and hence an increasing profit share in both countries.
Keywords: E12; E21; E22; E25; 330; Interest rate; distribution; demand; capital accumulation; Kaleckian model